Major Anthocyanin Pigments in the Ficus padana Fruits: HPLC-DAD-ESI-MS Identification and Antioxidant Activity - Daimon Syukri; Djaswir Darwis; Adlis Santoni (Universitas Gadjah Mada, 2014)
The anthocyanins in Ficus padana were extracted and identified by using high-performance liquid chromatography/diode array detection and electrospray ionization/mass spectrometry (HPLC-DAD-ESI-MS). The individual anthocyanins were identified by comparing between their mass spectral data and published data. The first compound (peak 1) was identify as a pelargonidin 3-(6”-p-coumarylglucoside)-5-(4”’-Malonylglucoside) and the second compound was identify as a pelargonidin 3-(6’’-Malonylglucoside). The second one is a major compound that taking up to 91% of the total anthocyanin content in F. padana extract. The antioxidant activity was determined with 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays and results showed that extract possessed high antioxidant capacity.